Dissemination of the Use of Reference Tools in Scientific Writing - Novri Gazali; Romi Cendra; Ahmad Rahmadani; Feby Elra Perdima; Mohammad Ashraf Khan; Noven Andrianto; Alim Komarudin (Peneliti Teknologi Teknik Indonesia, 2021)
This community service activity aims to improve students' skills and knowledge in using the reference tool in writing scientific papers. This community service activity was carried out on students of the Department of Physical Education Universitas Dehasen Bengkulu with 40 participants. Implementation methods in activities include: (1) Preparation Phase. At this stage the team did all the preparations for the implementation of the activity, starting from noting the number and readiness of the participants who would take part in the training and developing a WhatsApp Group to facilitate communication and distribution of materials before and during the training. In addition, at this stage the PKM team prepares PowerPoint materials about the Mendeley application which will be delivered starting from the introduction of the application, its benefits, how to install it to how to use it on a laptop. (2) Service Implementation Stage. At this stage, the material is delivered both how to install and use the Mendeley application and online training/practice guidance. (3) Evaluation Stage. At this stage the PkM team evaluates the implementation of activities by distributing a questionnaire via